Radiation hard optical links for the ATLAS SCT and Pixel detectors. - Charlton, D; Dowell, J; Homer, R; Jovanovic, P; Kenyon, I; Mahout, G; Shaylor, H; Wilson, J; Gregor, I; Nickerson, R; Mandic, I; Wastie, R; et al. (1999)
A full study of the optical readout package for the ATLAS SCT/Pixel detector data transmission is presented. Radiation hardness studies of VCSEL emitters, Epitaxial Silicon PIN diodes receivers and their associated chips have been carried out with fluences higher than 10(15)n.cm(-2) 1 MeV neutron equivalent and total ionising doses of 10 Mrad. The reliability was assessed by testing a large number of devices and accelerated ageing tests were also pursued over a period equivalent to more than the LHC operation time. Single Event Upset and magnetic field studies up to 6T have also been done on a new optical package design with positive results.